Biological and Molecular Characterization of a Jumbo Bacteriophage Infecting Plant Pathogenic Ralstonia solanacearum Species Complex Strains - Ahmad, Abdelmonim Ali; Addy, Hardian Susilo; Huang, Qi (Frontiers in Microbiology, 2021)
A jumbo bacteriophage infecting Ralstonia solanacearum species complex strains, designated RsoM2USA, was isolated from soil of a tomato field in Florida, United States, and belongs to the family Myoviridae. The phage has a long latent period of 270 min and completed its infection cycle in 360 min with a burst size of approximately 32 particles per cell. With a genome size of 343,806 bp, phage RsoM2USA is the largest Ralstonia-infecting bacteriophage sequenced and reported to date. Out of the 486 ORFs annotated for RsoM2USA, only 80 could be assigned putative functions in replication, transcription, translation including 44 tRNAs, and structure with the main structural proteins experimentally confirmed. Phylogenetic analyses placed RsoM2USA in the same clade as Xanthomonas phage XacN1, prompting a proposal of a new genus for the two jumbo phages. Jumbo phage RsoM2USA is a lytic phage and has a wide host range, infecting each of the three newly established Ralstonia species: R. solanacearum, R. pseudosolanacearum and R. syzygii, and significantly reduced the virulence of its susceptible R. solanacearum strain RUN302 in tomato plants, suggesting that this jumbo phage has the potential to be developed into an effective control against diseases caused by R. solanacearum species complex strains.